Design of OSMI‐4 Analogs Using Scaffold Hopping: Investigating the Importance of the Uridine Mimic in the Binding of OGT Inhibitors. (2nd March 2023) - Balsollier, Cyril; Tomašič, Tihomir; Yasini, Daniel; Bijkerk, Simon; Anderluh, Marko; Pieters, Roland J.
Abstract: β‐ N ‐Acetylglucosamine transferase (OGT) inhibition is considered an important topic in medicinal chemistry. The involvement of O‐GlcNAcylation in several important biological pathways is pointing to OGT as a potential therapeutic target. The field of OGT inhibitors drastically changed after the discovery of the 7‐quinolone‐4‐carboxamide scaffold and its optimization to the first nanomolar OGT inhibitor: OSMI‐4. While OSMI‐4 is still the most potent inhibitor reported to date, its physicochemical properties are limiting its use as a potential drug candidate as well as a biological tool. In this study, we have introduced a simple modification (elongation) of the peptide part of OSMI‐4 that limits the unwanted cyclisation during OSMI‐4 synthesis while retaining OGT inhibitory potency. Secondly, we have kept this modified peptide unchanged while incorporating new sulfonamide UDP mimics to try to improve binding of newly designed OGT inhibitors in the UDP‐binding site. With the use of computational methods, a small library of OSMI‐4 derivatives was designed, prepared and evaluated that provided information about the OGT binding pocket and its specificity toward quinolone‐4‐carboxamides. Abstract : β‐ N ‐Acetylglucosamine transferase (OGT) is a promising therapeutic target. The first nanomolar OGT inhibitor, OSMI‐4, is still the most potent inhibitor reported to date, yet its physicochemical properties limit its utility as a potential drug candidate and biological tool. To address this, we performed scaffold hopping, which yielded new OSMI‐4 derivatives, thus providing insight into the recognition features such as hydrogen bonding angles and desolvation penalties.